Poverty, social networks, and clientelism - Nico Ravanilla; Allen Hicken (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Why are the poor susceptible to clientelism, and what factors shield them from the influence of vote buying? We explore the role of both formal and informal social networks in shaping the likelihood of being targeted with private inducements. We argue that when the poor lack access to formal social networks, they become increasingly reliant on vote buying channelled through informal networks. To test our theory, we build the informal, family-based network linkages between voters and local politicians spanning a city in the Philippines. We then collect survey data on formal network connections, electoral handouts, and voting behaviour of 900 voters randomly drawn from these family networks. We show first that campaigns disproportionately target poorer voters. We then show that familial ties further influence targeting among poor voters. Finally, we show that access to formal networks such as workers' associations mitigate voter fears of punishment for failing to reciprocate.
Keywords: D72; O1; 330; social networks; poor; vote buying; clientelism; voting behaviour; Philippines